Life history traits associated with high fecundity help offset the worst genetic impacts of targeted poaching in Aquilaria sinensis - Wan-hin Kwok; Huarong Zhang; Feng Yang; Stephan W. Gale; Gunter A. Fischer; Richard M.K. Saunders (Global Ecology and Conservation, 2024)
Poaching is a global issue that threatens many species. However, little research attention has been paid to key life history traits that might help offset some of the worst genetic and demographic impacts of poaching. We investigate the onset of flowering and fecundity in Aquilaria sinensis, an agarwood-producing tree species that faces a constant threat of poaching throughout its native range in southern China. We hypothesise that certain life history traits in this species could buffer genetic erosion associated with selective poaching of larger individuals. We genotyped 1464 individuals using 15 microsatellite markers and examined the difference in genetic diversity between seedlings and adults, as well as that between individuals either side of the threshold diameter at breast height (DBH) size class targeted by poachers. Our study reveals that flowering commences at a DBH of 2.50 cm and that even trees at a DBH of about 6.9 cm invest heavily in seed-set, but that poachers tend to target individuals with a DBH of 15.25 cm or greater. No significant difference in genetic diversity was detected among individuals belonging to seedling and adult life-history stages, or between targeted and non-targeted size classes. The lack of such difference could be explained by certain life history traits which offset some of the most adverse impacts of poaching in Aquilaria sinensis, with important implications for the management and conservation of other species that are threatened by poaching.